IMPLEMENTASI PEMBELAJARAN SENI SUARA DAN MUSIK ANAK USIA DINI DI RA HABIBILLA - Hilda Zahra Lubis; Annisa Nasution; Astri Syakira Sunya; Latifah (Cendekia Madani Nusantara, 2024)
This research was conducted to find out about the implementation of sound arts and music learning for early childhood at RA Habibilla. The data from this research were collected through analysis and observation and using literature methods. The aim of the research is to discuss how teachers apply sound art and music learning for early childhood. It really needs to be discussed and studied to find out how it is implemented in the school.